INFLATION, BI 7 DAYS REPO RATE, AND JAKARTA COMPOSITE INDEX ON NET ASSET VALUE OF SHARIA MUTUAL FUND - Prabowo, Happy Irma Riyanti; Diana, Nana (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
This research purposed to examine the effect of inflation, BI 7 Days Repo Rate (BI7DRR), and Jakarta Composite Index on the net asset value of sharia mutual fund. The method used is the descriptive and derivative method with a quantitative approach, with multiple linear regression analysis to find the relationship between the variables. This study uses purposive sampling as the sampling technique, which is the sharia mutual fund registered in the Financial Services Authority of Indonesia. This research observed the variables in the period of 2016 to 2020 with monthly time series from secondary data. The findings result that partially, inflation has significant effect with negative direction on the net asset value of sharia mutual fund, while the BI7DRR and Jakarta Composite Index has insiginificant impact on the net asset value of sharia mutual fund. This result shows the investment behavior by investor where the inflation rate becomes a consideration whether to put their fund in investment, especially sharia mutual fund or more concern on their consumption. On the other side, the value of BI7DRR and the Jakarta Composite Index does not become investor's consideration to investing in sharia mutual fund. For simultaneous effect, inflation, BI7DRR, and Jakarta Composite Index have a significant effect on the net asset value of sharia mutual fund for 66%, which shows that the combined economic situation consisting of these factors can affect the movement of the net asset value of sharia mutual fund with a possibility of 66%, while 34% of the possibility left can be affected by variables outside this research.